Effects of immersive virtual reality exposure in preparing pediatric oncology patients for radiation therapy. (September 2021) - Tennant, Michelle; Anderson, Nigel; Youssef, George J.; McMillan, Laura; Thorson, Renae; Wheeler, Greg; McCarthy, Maria C.
Highlights: Virtual reality (VR) for paediatric patients is met with high acceptability. VR improves health literacy and understanding of pending radiation therapy procedures. Child and parent pre-procedural anxiety decreased following VR intervention. Abstract: Background: Procedural anxiety in children undergoing radiation therapy (RT) is common and is associated with poor procedural compliance and an increased used of general anaesthesia (GA). There is emerging evidence that Virtual Reality (VR) technology may reduce medical procedural distress through realistic and educative exposure to actual procedures via virtual simulation. Objective: To examine the feasibility, acceptability and efficacy of an Immersive VR exposure intervention aimed at reducing anxiety and enhancing preparedness for pediatric patients undergoing radiation therapy, and their parents. Method: A convenience sample of patients (6–18 years) scheduled for RT, and their parent caregivers, were recruited consecutively over a 14-month period. Patients were exposed to a virtual simulation of both CT Simulation (Phase 1) and RT (Phase 2), prior to these procedures occurring. Pre-and-post VR intervention measures (anxiety, health literacy) were administered across multiple time points. GA requirement following VR intervention was also recorded. Results: Thirty children and adolescents were recruited (88% participation rate). High VR acceptability and satisfaction was reported by patients, parents and radiation therapists. There were minimal adverse effects associated with VR. The VR intervention was found to improve children's understanding of the RT procedures (health literacy) and lower pre-procedural child and parental anxiety. Only one child in the study required GA (3.33%). Conclusions: This study provides novel and preliminary support for utilizing VR to prepare children and families for RT. Subsequent implementation of VR into routine paediatric RT has the potential to improve clinical and operational outcomes.